Wine Sensory Faults Origin, Prevention and Removal - Nunes, Fernando M.; Cosme, Fernanda; Filipe-Ribeiro, Luís (2022)
Wine is highly appreciated for its distinctive sensory characteristics, including its colour, aroma, and taste. However, unwanted microbiological activity, unbalanced concentrations of certain compounds resulting from unbalanced grape chemical compositions, and inadequate winemaking practices and storage conditions can result in sensory defects that significantly decrease wine quality. Although preventing wine defects is the best strategy, they are sometimes difficult to avoid. Therefore, when present, several fining agents or additives and technologies are available or being developed with different performances regarding their impact on wine quality. Wine stabilisation refers to removal and prevention strategies and treatments that limit visual, olfactory, gustatory, or tactile wine defects, as well as increase wine safety and stability through fining and the application of different operations carried out in wineries (filtration, pasteurisation, electrodialysis, and cold stabilisation) and the use of emerging technologies (electron-beam irradiation, high hydrostatic pressure, pulsed electric fields, ultrasound, pulsed light). Future trends in this field involve using more sustainable and environmentally friendly fining agents and technologies and developing treatments with better performance and specificity.